2016
DOI: 10.1016/j.jalz.2016.06.1795
|View full text |Cite
|
Sign up to set email alerts
|

P3‐136: A Genetically Immortalized Human Stem Cell Line: A Promising New Tool for Alzheimer’s Disease Therapy

Abstract: Amyloid-β peptides and hyper-phosphorylated tau are the main pathological hallmarks of Alzheimer's disease (AD). Given the recent failure of several large-scale clinical trials and the lack of disease-modifying pharmacological treatments, there is an urgent need to develop alternative therapies. A clinical grade human CTX0E03 neural stem cell line has recently passed phase I trials in people with stroke. However, this cell line has not been investigated in other neurodegenerative disorders. This study investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…The ability of CTX0E03 cells to survive in an in vitro model of Alzheimer’s disease was assessed by Puangmalai et al by culturing in an environment containing various concentrations of amyloid β or okadaic acid, a protein phosphatase inhibitor that creates a high concentration of phosphorylated tau protein. The CTX0E03 cell line demonstrated similar or better survival rates compared to primary cultured rat neuronal stem cells, making them potential candidates for cell therapy in Alzheimer’s disease [ 42 ]. At the same time, the study of Yoon et al demonstrated the effectiveness of using CTX0E03 cells for the treatment of Huntington’s disease in the quinolinic acid-lesioned mouse model [ 43 ].…”
Section: Immortalized Cells In Regenerationmentioning
confidence: 99%
See 1 more Smart Citation
“…The ability of CTX0E03 cells to survive in an in vitro model of Alzheimer’s disease was assessed by Puangmalai et al by culturing in an environment containing various concentrations of amyloid β or okadaic acid, a protein phosphatase inhibitor that creates a high concentration of phosphorylated tau protein. The CTX0E03 cell line demonstrated similar or better survival rates compared to primary cultured rat neuronal stem cells, making them potential candidates for cell therapy in Alzheimer’s disease [ 42 ]. At the same time, the study of Yoon et al demonstrated the effectiveness of using CTX0E03 cells for the treatment of Huntington’s disease in the quinolinic acid-lesioned mouse model [ 43 ].…”
Section: Immortalized Cells In Regenerationmentioning
confidence: 99%
“…Despite some issues with the methodology of clinical trials (small sample size, wide range of time elapsed since stroke, lack of female patients in phase I [ 44 , 45 ]), many preclinical [ 42 , 43 , 46 ] and clinical studies demonstrate that the CTX0E03 cell line is a promising therapeutic tool with a significant neuroregenerative potential, both in models of ischemic damage and in models of neurodegenerative diseases. The advantages of this line in comparison with the primary culture are obvious, such as the absence of the need for obtaining and isolating material and the standardization of research results.…”
Section: Immortalized Cells In Regenerationmentioning
confidence: 99%